1997
DOI: 10.1021/ma970629v
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interface of Heterogeneous Blends of Polycarbonate and Polyfluorostyrene by 13C−19F REDOR NMR

Abstract: Blends of one part of carbonyl-13 C, ring-13 C, or methyl-13 C-labeled polycarbonate with nine parts of poly(p-fluorostyrene) or poly(o-fluorostyrene) have been examined by 13C−19F rotational-echo double-resonance NMR. The immiscible blends were formed by precipitation from choloroform solution into methanol. After being annealed at 180 °C, the blends consist of domains of polycarbonate (average diameter of 36 nm) dispersed in a matrix of polyfluorostyrene. There are no kinetically trapped polycarbonate chains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The rotational-echo double-resonance (REDOR) , and transferred-echo double-resonance (TEDOR) , techniques introduced recently by Schaefer and co-workers have been utilized in structural investigations of a diverse range of materials including peptides, proteins, , polymers, , molecular sieves, and inorganic materials. For samples containing isolated IS spin pairs, it has been clearly demonstrated that reliable heteronuclear distances (which are in very good agreement with those determined from X-ray diffraction measurements) can be obtained using CP, REDOR, and TEDOR experiments. ,, …”
Section: Introductionmentioning
confidence: 95%
“…The rotational-echo double-resonance (REDOR) , and transferred-echo double-resonance (TEDOR) , techniques introduced recently by Schaefer and co-workers have been utilized in structural investigations of a diverse range of materials including peptides, proteins, , polymers, , molecular sieves, and inorganic materials. For samples containing isolated IS spin pairs, it has been clearly demonstrated that reliable heteronuclear distances (which are in very good agreement with those determined from X-ray diffraction measurements) can be obtained using CP, REDOR, and TEDOR experiments. ,, …”
Section: Introductionmentioning
confidence: 95%
“…2, top) has substantial contributions from carbons that are in the polystyrene core as well as from carbons in the poly-(acrylic acid)-polyacrylamide shell. Qualitatively, this result indicates that some of the fluorotryptophan must be near the core-shell interface (Tong and Schaefer, 1997). The radius of the SCK is 14 nm (Fig.…”
mentioning
confidence: 83%